Changes in kidney tissue and effects of erythropoietin after acute heart failure - ERCAN, FERİHA (TAYLOR & FRANCIS LTD, 2018)
Impairment of cardiac function causes renal damage. Renal failure after heart failure is attributed to hemodynamic derangement including reduced renal perfusion and increased venous pressure. One mechanism involves apoptosis and is defined as cardiorenal syndrome type 1. Erythropoietin (EPO) is a cytokine that induces erythropoiesis under hypoxic conditions. Hypoxia inducible factor 1 alpha (HIF-1 alpha) plays a regulatory role in cellular response to hypoxia. Protective effects of EPO on heart, kidney and nervous system are unrelated to red blood cell production. We investigated early changes in and effects of EPO on renal tissues of rats with myocardial infarction by morphology and immunohistochemistry. Coronary artery ligation was used to induce myocardial infarction in Wistar rats. Group 1 comprised sham operated rats; groups 2, 3 and 4 included rats after coronary artery ligation that were sacrificed 6 h after ligation and that were treated with saline, 5,000 U/kg EPO or 10,000 U/kg EPO, respectively; group 5 included rats sacrificed 1 h after ligation. Group 2 showed increased renal tubule damage. Significantly less tubule damage was observed in EPO treated groups. EPO and EPO receptor (EPO-R) immunostaining intensities increased slightly for group 5 and became more intense for group 2. EPO and EPO-R immunostaining was observed in the interstitial area, glomerular cells and tubule epithelial cells of EPO treated groups. HIF-1 immunostaining was observed in collecting tubules in the medulla only in group 2. Caspase-3 immunostaining is an indicator of apoptosis. Caspase-3 staining intensity decreased in renal medulla of EPO treated groups. EPO treatment may exert a protective effect on the renal tissues of patients with cardiorenal syndrome.
Keywords: cardiorenal syndrome; caspase-3; erythropoietin; hypoxia inducible factor 1 alpha (HIF-1 alpha); kidney; myocardial infarction; receptors; ACUTE-RENAL-FAILURE; HYPOXIA-INDUCIBLE FACTOR-1-ALPHA; CARDIORENAL SYNDROME TYPE-1; MYOCARDIAL-INFARCTION; CARDIOGENIC-SHOCK; TUBULAR CELLS; RAT KIDNEYS; INJURY; PROTECTS; HIF-1